2019
DOI: 10.1001/jamacardio.2019.0275
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Atherosclerotic Phenotype and Plaque Healing in Patients With Recurrent Acute Coronary Syndromes Compared With Patients With Long-term Clinical Stability

Abstract: IMPORTANCE At one end of the coronary artery disease (CAD) spectrum, there are patients with multiple recurrent acute coronary syndromes (rACS), and at the other end there are those with long-standing clinical stability. Predicting the natural history of these patients is challenging because unstable plaques often heal without resulting in ACS. OBJECTIVE To assess in vivo the coronary atherosclerotic phenotype as well as the prevalence and characteristics of healed coronary plaques by optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 26 publications
8
70
0
2
Order By: Relevance
“…This healthy user bias is a confounder and difficult to quantify, but has to be considered when interpreting the evidence presented by Lassenius et al Interestingly, upon stratification by sex (as depicted in the Cox model of recurrent events in Table 3), levels of LDL-C were no longer significantly associated with event recurrence in males. 4 While this may be attributable to a loss of power caused by the splitting of the groups, these data align with data by Vergallo et al, 6 where the expression of markers of atherogenic dyslipidaemia, but not LDL-C, discriminated between patients with multiple recurrent acute coronary syndromes and long-standing clinical stability, as outlined in further detail below. 7,8 Taken together, Lassenius et al showed in a large cohort representing real life that a substantial number of patients did not reach their LDL-C goal and that statin adherence decreased over time.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This healthy user bias is a confounder and difficult to quantify, but has to be considered when interpreting the evidence presented by Lassenius et al Interestingly, upon stratification by sex (as depicted in the Cox model of recurrent events in Table 3), levels of LDL-C were no longer significantly associated with event recurrence in males. 4 While this may be attributable to a loss of power caused by the splitting of the groups, these data align with data by Vergallo et al, 6 where the expression of markers of atherogenic dyslipidaemia, but not LDL-C, discriminated between patients with multiple recurrent acute coronary syndromes and long-standing clinical stability, as outlined in further detail below. 7,8 Taken together, Lassenius et al showed in a large cohort representing real life that a substantial number of patients did not reach their LDL-C goal and that statin adherence decreased over time.…”
supporting
confidence: 84%
“…11 The lipoprotein pattern referred to as atherogenic dyslipidaemia is a prominent lipid trait associated with metabolic syndrome and ASCVD. 12 Interestingly, in a recent study by Vergallo et al, 6 neither LDL-C level nor statin use discriminated between patients with multiple recurrent acute coronary syndromes and long-standing clinical stability. 7 Conversely, global inflammatory burden (hsCRP levels) and the expression of atherogenic dyslipidaemia were higher in the recurrent acute coronary syndrome group compared with the long-standing stable angina group, with high-density lipoprotein cholesterol (HDL-C) levels showing statistical significance.…”
mentioning
confidence: 94%
“…61 Furthermore, the TG/HDL-C ratio has been linked to plaque phenotype and clinical stability in coronary artery disease: the ratio was significantly higher in patients with TCFAs than in those without, and it was nonsignificantly higher in patients with multiple recurrent acute coronary syndromes than in those with long-standing stable angina. [82][83][84] Of note, triglycerides and the TG/HDL-C ratio do not reliably predict insulin resistance in African Americans. This has been linked to the observation that insulin resistance does not impair lipoprotein lipase in this subgroup and thus does not induce hypertriglyceridemia.…”
Section: Insulin Resistance/compensatory Hyperinsulinemia/prediabetesmentioning
confidence: 99%
“…In a recent ex vivo study investigating the accuracy of OCT for diagnosing healed ruptured plaques, Shimokado et al proposed the presence of layered structures in the conventional OCT intensity signal as a predictor of histologically determined healed ruptures of coronary plaques (75). Furthermore, clinical studies have demonstrated that layered structure in superficial plaques identified by OCT are associated with plaque vulnerability or rapid progression of coronary artery stenosis (10,76), although there remains some controversy and another study found similar features to indicate enhanced plaque stability (23). Despite the importance of assessing the healing process of coronary thrombus, the conventional OCT intensity image provides limited insight into the process of thrombus organization.…”
Section: Polarization Signatures Of Acute and Organizing Thrombusmentioning
confidence: 99%
“…Also, it is now a well-accepted concept that plaque rupture and erosion frequently occur silently without causing clinical symptoms, emphasizing the crucial role of vascular healing in determining the fate of a lesion (1,21). Therefore, the mechanisms that impair vascular healing are increasingly investigated to explain disease progression and the development of ACS (22)(23)(24). Following stent implantation, vascular healing and tissue response play a similar decisive role in defining the risk of stent failure and future complications (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%